Evaluation of Wide Corneal Epithelial Remodeling after Small Incision Lenticule Extraction (SMILE) with Wide-Field Optical Coherence Tomography. (20th March 2022) - Ye, Yiming; Chen, Pei; Yu, Na; Wan, Linxi; Lan, Min; Zheng, Hua; Yu, Keming
Abstract : Purpose . This study aims to assess the corneal epithelial remodeling within a 9 mm diameter zone induced by small incision lenticule extraction (SMILE) and evaluate its relationship with the refractive outcomes. Methods . A total of 64 eyes of 64 patients were included. Wide-field optical coherence tomography (OCT) was used to measure the epithelial thickness (ET) across a 9 mm diameter area, preoperatively, and after one day, one week, one month, three months, and six months postoperatively. The ET changes were compared among the different time points and analyzed zones. Results . The ET increases from one week to three months and stabilized from three months to six months. Compared to the preoperative values, the mean ET changes at six months in central (2 mm), paracentral (2–5 mm), mid-peripheral (5–7 mm), and peripheral (7–9 mm) zones were 4.37, 4.36, 1.61, and −1.59 μ m, respectively. The correlation between the epithelial thickening and the amount of myopia correction was positive in central (P = 0.001) and paracentral zones (P < 0.001) and negative in peripheral zone (P = 0.006). The intended diameter of the optical zone was negatively related to epithelial hyperplasia in the central (P = 0.020) and paracentral zone (P = 0.006), and the correlation was positive in the mid-peripheral zone (P = 0.001). The epithelial thickening of central zone (P = 0.012) and the difference of mean ET between central and paracentral zone (P = 0.020) were negatively related to the spherical equivalent at six months. Conclusion . An asymmetric lenticule-like pattern of epithelial remodeling occurred in 9 mm diameter cornea at six months after myopic SMILE. The epithelial remodeling may affect the refractive outcomes of SMILE.